(untitled) (Research, Society and Development, 2020)
Sulphated fertilizers, gypsum and organic matter are sources containing sulfur (S) which aids in growth and chemical composition of brassicas. Studies with S in collard greens (Brassica oleracea L.var. acephala) are rare. The objective of this work was to evaluate use of gypsum and organic compost at planting, followed by ammonium sulphate topdressing, on yield of collard greens. Treatments: organic compost (30 t ha-1), or gypsum (1.2 t ha-1) individually, organic compost plus gypsum. Total sulfur applied at 0; 93.31; 186.69, or 280 kg ha-1, corresponding to 0; 465.5; 931 or 1400 kg ha-1 of ammonium sulphate, was divided into 7 applications. The N was fixed (280 kg∙ha-1), and complemented with 630, 415.1, 208.6 or 0 kg∙ha-1 of urea. At 30 DAT, the first leaf samples, minimum of 20 cm in length, were collected; additional leaves were harvested every 10 days, in a total of 8 harvests. After each harvest total length (including leaf petiole), and leaf number per plant, width, and fresh weight were evaluated. Soil amendment and sulfur dose did not influence yield, and urea or ammonium sulfate can be used as a source of N. No symptoms of sulfur deficiency occurred and plants averaged 15.6 t ha-1 of leaves.